India-Nepal Relationship AFTER Modi's Rise: Understanding the Impact of Modi's Visit and Ongoing Challenges in India-Nepal Relations (Journal of Advances and Scholarly Researches in Allied Education, 2022)
As an independent nation, Nepal seeks to establish fair relations with India, as this article triesto explain. Nepal is closer to India than any other country in terms of geography, culture, and economics.Nepal has also come to terms with the fact that it cannot ignore its southern neighbor India. With the1950 Indo-Nepal Treaty of Peace and Friendship and the accompanying secret letters that definedsecurity relations between the two countries, as well as an agreement governing both bilateral trade andtrade transiting Indian Territory, the Federal Democratic Republic of Nepal and the Republic of Indiaofficially began their relationship. As part of his neighborhood first strategy, Modi made his first visitto Nepal in August 2014. As the first foreign leader to address the Constituent Assembly, which isresponsible for writing Nepal's new constitution, he had an important role to play. With his words, theIndian government looked to be signaling a new era in India–Nepal relations, drawing plaudits from allpolitical groups in Nepal. The Ministry of External Affairs (MEA) in New Delhi released a series ofremarks expressing India's disapproval with Nepal's constitution. Within days after the constitution'senactment, Indian Express cited MEA sources and distributed a seven-point petition for revisions. Asignificant humanitarian catastrophe has been triggered by the election of nationalistic politician K P Olias prime minister in Nepal, which has resulted in a widening of the divide between Delhi and Kathmandu,with no prospect of reconciliation in sight.